1998
DOI: 10.2116/analsci.14.501
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Liquid Extraction of Metal Ions with a Cyclic Ligand Calixarene Carboxyl Derivative

Abstract: Numerous studies have been performed to develop efficient separation and concentration processes of metals with a solvent-extraction technique, which is well known to be one of the promising techniques to separate and concentrate metals on an industrial scale. The extractant is known to have a crucial effect on the separation and extraction efficiency in the solvent-extraction process. Therefore, it is very important to develop an efficient extractant for a target metal ion. Thus, the choice of the extractant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Naturally the waste materials from related industries have been highlighted as valuable resources themselves and a number of groups have been working on recovery of rare earth metals from such sources. The use of calixarenes has been reported as useful extractants for metal ions [279][280][281][282][283][284][285][286][287], but the sol- ubility of these complexes has limited their usefulness. Kubota et al developed a novel calix [4]arene carboxyl derivative which showed remarkably high selectivity for the rare earth metals compared to commercially available extractants, PC-88A and Versatic 10 [288] (Fig.…”
Section: Fluorescence/luminescencementioning
confidence: 99%
“…Naturally the waste materials from related industries have been highlighted as valuable resources themselves and a number of groups have been working on recovery of rare earth metals from such sources. The use of calixarenes has been reported as useful extractants for metal ions [279][280][281][282][283][284][285][286][287], but the sol- ubility of these complexes has limited their usefulness. Kubota et al developed a novel calix [4]arene carboxyl derivative which showed remarkably high selectivity for the rare earth metals compared to commercially available extractants, PC-88A and Versatic 10 [288] (Fig.…”
Section: Fluorescence/luminescencementioning
confidence: 99%
“…The alkali salt was added to both the feed and the receiving phases such that both phases had the same ionic strength. As the cavity of t Oct[6]CH 2 COOH can encapsulate large alkali ions, the order that the alkali ions are extracted in depends on ionic radius [31]. Therefore, the extraction of Cyt-c is significantly inhibited in the presence of large alkali ions such as cesium ions.…”
Section: Factors That Influence the Transport Of Cytochrome Cmentioning
confidence: 99%
“…The shape of the curves indicates that it is possible, applying the McCabe-Thiele method of calculation, to perform the extraction in one or two stages [15], reaching a very low concentration of silver in the raffinate (depending on the demands for an outlet concentration), as is illustrated in Fig. 5b.…”
Section: Extraction Isothermsmentioning
confidence: 97%
“…The effectiveness of calixarenes to extract noble metals from highly acidic media is a particularly good feature of these oligomolecules. Solvent extraction of heavy metals, such as mercury, cadmium, lead and copper, in mixture with different noble metals, has also been investigated [7][8][9]15]. Some of calixarenes can efficiently extract even anions such as, for example, chromate or acetate anions [3,14].…”
Section: Introductionmentioning
confidence: 99%